Freedom at the Tip of the Pedal: A Metaphor Study - Senem Çeyiz; Velittin Balcı (ümit doğan üstün, 2021)
The aim of this study was to reveal the perceptions of bicyclests' about bicycle and cycling through metaphors. It is thought that the findings obtained for the purpose of the research will contribute to the studies to be made in order to spread the use of bicycles in the society. For this purpose, the phenomenology model, one of the qualitative research approaches, was used in the research. 76 bicyclists selected by the purposive sampling method were included in the study. In the data collection phase, a personal information form and a form composed of semi-structured sentences created by the researchers were used. In the analysis of the data; content analysis method was used. During the analysis of the data, the metaphors created by the participants regarding the concepts of "Bicycle" and "Cycling" were listed and categorized. The categories created from the metaphors obtained within the scope of the research indicate that cycling is an activity that reflects the difficulties and beauties of life, makes feeling free and happy, contributes to physical and mental development, and has risks from infrastructure deficiencies. In addition, it is seen that participants identify bicycle with happiness and develop emotional commitment with their bicycles.